Cascaded Nonlinear Control of a Duocopter with Disturbance Compensation by an Unscented Kalman Filter. Issue 1 (2015) - Aschemann, Harald; Meinlschmidt, Thomas
Abstract: A cascaded control strategy for an innovative Duocopter test rig - a helicopter with two rotors combined with a guiding mechanism - is presented in this paper. The guiding mechanism consists of a rocker arm with a sliding carriage that enforces a planar workspace of the Duocopter. The Duocopter is attached to the carriage by a rotary joint and offers 3 degrees of freedom. The derived system model has similarities with a PVTOL and a planar model of a quadrocopter but involves additional terms due to the guiding mechanism. In the paper, a model-based cascaded control strategy is proposed: in the outer MIMO control loop, sliding mode techniques are employed to control both the horizontal and the vertical Duocopter position. The rotation angle of the Duocopter is controlled in a linear inner control loop using flatness-based techniques. An additional feedforward control takes into account known parts of the coupling forces between the carriage and the rocker. The control structure is extended by an Unscented Kalman Filter (UKF) that provides estimates for the state vector and, moreover, estimates for remaining errors concerning the feedforward coupling forces. The sum of the feedforward part and the estimated part can be used to accurately compensate for the impact of the guiding mechanism on the motion of the Duocopter frame. Thereby, an excellent tracking performance in vertical and horizontal direction can be achieved. The efficiency of the proposed control strategy is demonstrated by experiments.